Rancang Bangun Sistem Informasi Koperasi SMA Negeri 1 Bumiayu Berbasis Web - Mabruri, Rifqi Tri; Setyorini, Arifah Indah; Muafy, Bagus Izzan (Pendidikan Teknologi Informasi Universitas Bumigora, 2023)
The cooperative information system for SMA Negeri 1 Bumiayu is a computer-based application that aims to manage and facilitate cooperative operations within the school environment. The system is designed to help manage administration, finance, inventory, and transactions with consumers in a more structured and efficient manner. The cooperative information system for SMA Negeri 1 Bumiayu will provide benefits to various parties such as collective management and cooperative members who manage finances, be able to make decisions based on accurate information, easily access cooperative information, and monitor membership contributions. The benefits provided to consumers are in the form of convenience in transactions that can be made online with e-money, a list of items that can be monitored without having to come to the cooperative. They can arrange transaction times according to needs. The customers consist of teachers, staff, and SMA Negeri 1 Bumiayu students. With the implementation of the cooperative information system, the transaction process will be able to increase the effectiveness and efficiency of cooperative operations. In addition, this information system can provide a better experience for cooperative members in managing finances, improve business skills, and build awareness of the importance of cooperation and responsibility in the school environment.